2011
DOI: 10.1111/j.1600-051x.2011.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periodontal therapy on GCF cytokines in generalized aggressive periodontitis subjects

Abstract: Aim To examine changes in levels of gingival crevicular fluid (GCF) cytokines, after periodontal therapy of generalized aggressive periodontitis (GAgP). Materials and Methods Twenty five periodontally healthy and 24 GAgP subjects had periodontal clinical parameters measured and gingival crevicular fluid (GCF) samples collected from up to 14 sites/subject. GCF samples were analyzed using multiplex bead immunoassay for: GM-CSF, IFN-γ, IL-10, IL-1β, IL-2, IL-6 and TNF-α. Aggressive periodontitis subjects were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 40 publications
(51 reference statements)
8
71
1
4
Order By: Relevance
“…It was demonstrated that periodontal therapy improved GCF cytokine profiles by lowering IL-1β and increasing IL-10 levels but the mean change in IL-10 did not differ between AgP and control groups. 29 Similarly, these findings were observed in our previous study. 7 In the literature, there are few studies investigating the relationship between AgP and IL-6 gene polymorphisms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It was demonstrated that periodontal therapy improved GCF cytokine profiles by lowering IL-1β and increasing IL-10 levels but the mean change in IL-10 did not differ between AgP and control groups. 29 Similarly, these findings were observed in our previous study. 7 In the literature, there are few studies investigating the relationship between AgP and IL-6 gene polymorphisms.…”
Section: Discussionsupporting
confidence: 79%
“…We showed that reduced clinical inflammation was related to lower GCF IL-6 cytokine level. Contrary to our study, Oliveira et al 29 reported that GCF IL-6 level was increased in GAgP patients after treatment, but not significantly. The authors explained this situation by affirming that IL-6 acts both as pro-and anti-inflammatory cytokine at the same time.…”
Section: Discussioncontrasting
confidence: 54%
“…They can also be used to discriminate healthy subjects from patients with AgP [41, 51, 80, 99]. Owing to the slight differences in IL-1 β levels between healthy and gingivitis sites [41, 51, 103], it is difficult to use them as indicators or predictors for disease initiation from healthy status to gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…Sterile paper strips (Periopaper Strip ® Collection, Oraflow, Plainview, NY, USA) were then inserted for 30 seconds. 20 Samples visibly contaminated with blood were discarded. The volume Lost to follow-up: n = 0 n = 7 with complete data n = 7 analyzed…”
Section: Clinical Examinationmentioning
confidence: 99%